2011
DOI: 10.1108/09513541111136667
|View full text |Cite
|
Sign up to set email alerts
|

Fostering independent learning and engagement for postgraduate students

Abstract: PurposeAs educational technologies are more widely adopted in higher education teaching and learning, publishers often include online resources to accompany their textbook offerings. The purpose of this paper is to report the results of a study forming part of a larger ongoing evaluation of the third party software product WileyPLUS.Design/methodology/approachThe paper describes the integration of the publisher's tools into a specific curriculum context and takes a critical look at the pedagogical effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…When they experienced a lack of understanding around the rules of the classroom, a reluctance to participate was demonstrated. Blount and McNeill (2011) provide further support for this lack of confidence, suggesting that from their research they found postgraduate students needed support to build their confidence surrounding the use of technology (an issue which is prominent in many postgraduate students' academic lives).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When they experienced a lack of understanding around the rules of the classroom, a reluctance to participate was demonstrated. Blount and McNeill (2011) provide further support for this lack of confidence, suggesting that from their research they found postgraduate students needed support to build their confidence surrounding the use of technology (an issue which is prominent in many postgraduate students' academic lives).…”
mentioning
confidence: 99%
“…The authors comment that 'Issues of confidence, identity, self-presentation and social comparison clearly loomed large and were of paramount importance to these students' (p156), findings which would seem to contrast with assumptions of expertise and reveal the importance of exploring postgraduate student participation in their studies. In another study by Blount and McNeill (2011) postgraduate students were found to require support to enable engagement with educational technology and moreover, such technology needed to be seen to be part of the curriculum to prompt engagement. In our own work referred to above (Tobbell et al, 2010) students highlighted the need for personal tutors to help them negotiate their study.…”
mentioning
confidence: 99%
“…Today, there are many software packages available from textbook publishers and other vendors which can be used to improve the instruction and learning process; but as stated by Blount and McNeil in their study, the software must be carefully integrated into the curriculum and students must be supported in its use (Blount & McNeil, 2011). If so, it proves to be a very effective tool.…”
Section: Adopting Other Software and Resources As A Learning Toolmentioning
confidence: 99%
“…Further research [6] reports that postgraduate students need to see the learning advantages of any technology and importantly, that they require specific support in order to fully engage. Falloon's work with postgraduates participating in a virtual classroom found that trust and rapport with other students were important and that in order to encourage engagement participants needed to identity with the group, any uncertainty resulted in withdrawal [7].…”
Section: 'I'm Not the Only One Who Is Losing Sleep And Even Feelinmentioning
confidence: 99%